Development of a flattening filter free multiple source model for use as an independent, Monte Carlo, dose calculation, quality assurance tool for clinical trials. Issue 9 (1st August 2017) - Faught, Austin M.; Davidson, Scott. E.; Popple, Richard; Kry, Stephen F.; Etzel, Carol; Ibbott, Geoffrey S.; Followill, David S.
Abstract : Purpose: The Imaging and Radiation Oncology Core‐Houston (IROC‐H) Quality Assurance Center (formerly the Radiological Physics Center) has reported varying levels of compliance from their anthropomorphic phantom auditing program. IROC‐H studies have suggested that one source of disagreement between institution submitted calculated doses and measurement is the accuracy of the institution's treatment planning system dose calculations and heterogeneity corrections used. In order to audit this step of the radiation therapy treatment process, an independent dose calculation tool is needed. Methods: Monte Carlo multiple source models for Varian flattening filter free (FFF) 6 MV and FFF 10 MV therapeutic x‐ray beams were commissioned based on central axis depth dose data from a 10 × 10 cm 2 field size and dose profiles for a 40 × 40 cm 2 field size. The models were validated against open‐field measurements in a water tank for field sizes ranging from 3 × 3 cm 2 to 40 × 40 cm 2 . The models were then benchmarked against IROC‐H's anthropomorphic head and neck phantom and lung phantom measurements. Results: Validation results, assessed with a ±2%/2 mm gamma criterion, showed average agreement of 99.9% and 99.0% for central axis depth dose data for FFF 6 MV and FFF 10 MV models, respectively. Dose profile agreement using the same evaluation technique averaged 97.8% and 97.9% for the respective models. Phantom benchmarking comparisons were evaluated with a ±3%/2 mm gamma criterion, and agreement averaged 90.1% and 90.8% for the respective models. Conclusions: Multiple source models for Varian FFF 6 MV and FFF 10 MV beams have been developed, validated, and benchmarked for inclusion in an independent dose calculation quality assurance tool for use in clinical trial audits.